Presence Promotes Performance on a Virtual Spatial Cognition Task: Impact of Human Factors on Virtual Reality Assessment - Maneuvrier, Arthur; Decker, Leslie Marion; Ceyte, Hadrien; Fleury, Philippe; Renaud, Patrice (Frontiers in Virtual Reality, 2020)
The use of virtual reality in spatial cognition evaluation has been growing rapidly, mainly because of its potential applications in the training and diagnosis of cognitive impairment and its ability to blend experimental control and ecological validity. However, there are still many grey areas on virtual reality, notably on the sense of presence and its complex relationship to task performance. Performance in VR is often suggested to be influenced by other human factors amongst which cybersickness, gender, video game experience and field dependence. Would an individual experiencing more presence systematically show better performance? This study aimed to be part of a framework of virtual reality as this question is fundamental for rigorous assessment and diagnostic, and particularly in the spatial cognition field. 48 healthy young subjects were recruited to take part in a virtual spatial cognition evaluation. Spatial cognition performance, along with their level of presence, cybersickness, video game experience, gender and field dependence, were measured. Matrix correlations were used, along with linear regressions and mediation analysis. Results show that presence promoted performance on the spatial cognition evaluation, while cybersickness symptoms hindered it, notably among women. The presence – performance relationship was not mediated by other human factors. Video game experience significantly predicted both sense of presence and cybersickness, the latter two being negatively correlated. Even if women experienced more negative symptoms than men, gender appears less informative than cybersickness and video game experience. Field dependence was not associated with any other variable. Results are discussed by confronting two theories of cognition (representational versus ecological), highlighting that virtual reality is not a simple transposition of reality but truly a new paradigm with its own biases favoring some individual more than others, and that some human factors have to be controlled for rigorous uses of virtual environments, particularly for spatial cognition evaluation.